2006
DOI: 10.1123/apaq.23.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Aspects of Youth Disability Sport

Abstract: Psychosocial aspects of participation in youth disability sport were examined using social-cognitive theory and the sport commitment model. An international sample of athletes with disabilities (N = 112) reported high levels of sport commitment and sport enjoyment, perceived physical ability, and sport friendship quality. They perceived their parents to provide moderately strong levels of encouragement of their sport participation. Correlational analyses indicated moderate to strong relationships among sport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 45 publications
4
63
1
12
Order By: Relevance
“…Finally, since it has been suggested that sport may provide an effective avenue to combat the discrimination and stigma commonly experienced by individuals with disabilities (Giacobbi, Stancil, Hardin, & Bryant, 2008), research within this setting is warranted. Fortunately, there is growing support for the notion that sport can be a fertile developmental context for youth with disabilities (e.g., Kristén, Patriksson, & Fridlund, 2002;Martin, 2006). Previous research suggests that sport can have a positive influence on youth's development of new physical and social skills (Groff & Kleiber, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, since it has been suggested that sport may provide an effective avenue to combat the discrimination and stigma commonly experienced by individuals with disabilities (Giacobbi, Stancil, Hardin, & Bryant, 2008), research within this setting is warranted. Fortunately, there is growing support for the notion that sport can be a fertile developmental context for youth with disabilities (e.g., Kristén, Patriksson, & Fridlund, 2002;Martin, 2006). Previous research suggests that sport can have a positive influence on youth's development of new physical and social skills (Groff & Kleiber, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While previous research provides valuable insight into the types of positive developmental outcomes that may be acquired through sport, the existing literature predominantly focuses on the sport experiences of able-bodied athletes. Studies examining the sport experiences of athletes with disabilities are relatively limited in comparison (Martin, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are presented as means, standard deviations (SD), medians and ranges, which gave numbers that could be used across the categories (Imms, 2008). The relative indicator of participation frequency also indicates the mean amount of time that the children spent in the different activity categories (King et al, 2004;2006). Participation frequency in skill-based activities was somewhat lower than participation in physical activities.…”
Section: Diversity Of Activities and Frequency Of Participationmentioning
confidence: 99%
“…Martin (2006) The activity performed by the most Norwegian children was walking or hiking (85,9 %, Table 4). Although this activity is not categorised as a physical leisure activity on the CAPE or the PAC, it is still relevant among physical activities in a Norwegian context because it gives a typical picture of participation in physical activity for Norwegian children.…”
Section: Preferences and Enjoymentmentioning
confidence: 99%